Promoting or restricting competition? - The 50plus1-rule in German football - Oliver Budzinski; Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2020)
The 50plus1-rule in German football is a controversially discussed institution that regulates investment behavior of professional football teams. This paper discusses from a sports economics perspective the suspected market failures that the 50plus1-rule is expected to prevent. To examine the effects of the regulation empirically, we gathered panel data on 47 teams in the German Major League Football ("Erste Bundesliga") from the seasons 1989/90 until 2018/2019. Applying various approaches to measure financial and competitive imbalance in the league, we derive a growing trend of imbalance since the introduction of the 50plus1-rule. We employ a Difference-in-Differences approach to examine investment behavior in budgets and sporting success between afflicted competitors and those exempted from the rule. Our results do not suggest any equalizing properties of the regulation. We find anticompetitive effects and distorting properties of the regulation.
Keywords: Z23; Z21; Z2; J83; L11; L50; 330; 50plus1-rule; football; sports economics; financial regulation; investment; sport finance; soccer; competition economics